Special education : advancing values - Obiakor, Festus E.; Bakken, Jeffrey P. (Advances in special education, 2024)
Special education has changed over the years since its inception due to advocacy, litigation, legislation, trends, and research investigations. While it can be somewhat controversial depending on the disability the child might have or professionals involved in the process of instructing and planning his/her future education, it is a field that has values that has had measurable impacts on people's lives. Special Education: Advancing Values focuses on values that are engrained in special education and how we can maintain, sustain, and advance them. It also addresses the most current viewpoints and perspectives on the traditions of special education for students with disabilities alongside new and innovative practices. Special Education: Advancing Values is a very comprehensive book. The chapters introduce the field of special education and how we can maintain and advance traditions in the education of students with learning disabilities, emotional and/or behavioral disorders, intellectual disabilities, physical and other health impairments, students who are deaf/hard of hearing, students with visual impairments, and students with extensive support needs. Related topics include students from culturally and linguistically diverse backgrounds, general education teachers, school leaders and administrators, and parents. Special Education: Advancing Values concludes with a summary chapter that addresses why special education is an important educational phenomenon that has fundamental values worthy of sustainability and advancements. This volume is an excellent resource for special education professionals who teach and serve learners with disabilities, and other related professionals involved in the educational process such as administrators, school counsellors, and psychologists.